Balancing cognitive diversity and mutual understanding in multidisciplinary teams. Issue 1 (January 2017) - Mitchell, Rebecca; Boyle, Brendan; O'Brien, Rachael; Malik, Ashish; Tian, Karen; Parker, Vicki; Giles, Michelle; Joyce, Pauline; Chiang, Vico
Abstract : Background: Interprofessional health care teams are increasingly utilized in health care organizations. Although there is support for their capacity to solve complex problems, there is also evidence that such teams are not always successful. In an effort to understand the capacity of interprofessional teams to innovate successfully, we investigate the role of cognitive diversity to establish whether and how knowledge differences lead to innovation. Purposes: The aim of this study was to construct and investigate a model of team innovation predicted by cognitive diversity. In addition to investigating the direct impact of cognitive diversity in interprofessional health care teams, we develop a model incorporating mediated and moderated effects. In this study, we explore the role of debate as a mediating factor capable of explaining the impact of cognitive diversity on innovation. We further propose that the link between cognitive diversity and innovation through debate is contingent upon trans-specialist knowledge, knowledge shared by health care professionals, spanning specialist divides and enabling mutual understanding. Methodology: The hypotheses were investigated using a cross-sectional, correlational design. Survey data received from 75 interprofessional teams employed in an acute care setting, representing a 36% response rate, were used to investigate our model. Findings: Analysis supports a significant relationship between cognitive diversity and debate, which is stronger when teams rate highly for trans-specialist knowledge. Results also support a positive relationship between debate and innovation and our full moderated mediated pathway. Practice Implications: A range of strategies are indicated by our results to increase innovation in interprofessional teams. In particular, interventions such as interprofessional education and training, which have been shown to facilitate the development of shared language and meaning, are recommended by our findings.